2002
DOI: 10.1067/mai.2002.126781
|View full text |Cite
|
Sign up to set email alerts
|

CD40 engagement enhances eosinophil survival through induction of cellular inhibitor of apoptosis protein 2 expression: Possible involvement in allergic inflammation

Abstract: Background: CD40 engagement enhances eosinophil survival, suggesting a role for this receptor in the development of eosinophilia. Objective: We examined whether CD40 enhances eosinophil survival by inducing the expression of antiapoptotic proteins. Three members of the inhibitor of apoptosis protein (IAP) family, namely cellular (c)-IAPl, C-IAP2, and XIAP, and 2 antiapoptotic proteins of the Bcl-2 family, namely Bcl-x L and Bfl-1/A1, were investigated. Methods: Blood and sputum were obtained from healthy subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…This cell cycle configuration is typical of cells that are undergoing active proliferation. These data are compatible with those of previous reports on the effects of CD40 in other cell types (26,27,32).…”
Section: Discussionsupporting
confidence: 83%
“…This cell cycle configuration is typical of cells that are undergoing active proliferation. These data are compatible with those of previous reports on the effects of CD40 in other cell types (26,27,32).…”
Section: Discussionsupporting
confidence: 83%
“…In addition, WOOLLEY et al [5] demonstrated an increase in the sputum eosinophil AR and a decrease in sputum eosinophil numbers following corticosteroid treatment of patients with induced asthma exacerbation. Therefore, delayed eosinophil apoptosis may be an important cause of the increased tissue load of eosinophils seen in asthma [9,10]. However, a recent study by GIBSON et al [8] investigating the anti-inflammatory effects of a single high dose of inhaled budesonide reported that a subsequent decrease in the percentage sputum eosinophils following treatment was not accompanied by an increase in the proportion of apoptotic eosinophils.…”
Section: Discussionmentioning
confidence: 90%
“…However, to date there have been few studies that have utilised this technique to compare the relationship between measures of eosinophil apoptosis or survival in induced sputum with clinical and functional parameters of disease severity [5][6][7][8][9][10]. The authors hypothesised that there is a relationship between reduced eosinophil apoptosis and both a global clinical severity score and separate components of the asthma phenotype.…”
mentioning
confidence: 99%
“…Thus, its expression is tightly regulated both at the transcriptional and translational levels. Indeed, in certain instances, cIAP2 mRNA is present in the absence of cIAP2 protein (1,30).…”
mentioning
confidence: 99%